High-Performance Metamaterial Light Absorption from Visible to Near-Infrared Assisted by Anti-Reflection Coating - Dongqing Wu; Lei Lei; Meiting Xie; Ping Xu; Shixiang Xu (Photonics, 2023)
This study experimentally demonstrates two types of ultra-broadband metamaterial absorbers with high performance in the visible-to-near-infrared range by using different anti-reflection coatings (i.e., SiO2 and Si3N4) and a multi-subcell Ti-SiO2-Ti metasurface. Compared to the bare metamaterial nanostructure, the absorption bandwidth of the coated metasurfaces exhibit increases of 594 nm and 1093 nm, respectively. Such improvements benefit from nearly perfect impedance matching to the free space enhanced by the anti-reflection coating, thin film interference, and excitations of different surface plasmon resonances. As a result, the absorber with SiO2 coating exhibits a measured bandwidth with an absorption of 0.9 ranging from 502 nm to 1892 nm, while the absorber with Si3N4 coating further broadens the bandwidth from 561 nm to 2450 nm. The measured average absorptions for both cases remain above 95% and 87%, respectively. Moreover, both nanostructures are robust to large incident angles of up to 60° for both TE and TM modes. Our findings highlight the promising potential of these absorbers for various applications, including solar energy harvesting, thermal emitters, and photodetectors.